Optimizing Teacher Competence through Technology - Enhanced Lesson Planning and Assesment - Yumna Nabila; Zainal Arifin; Muhamad Lazuardi Pradivta Komara (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
The rapid development of digital technology presents significant challenges for the education sector, particularly for teachers who began teaching before the year 2000 and still struggle to utilize technology, including in administrative tasks and assessment activities. This condition creates a competency gap between teachers and 21st-century students who are far more adaptive to technology, affecting the effectiveness of teaching and learning processes as well as teacher professionalism. Similar issues are still found at SMAN 1 Sliyeg, a school established in 1997 and recognized as one of the leading high schools in Indramayu Regency. This situation is further reinforced by the demands of the Kurikulum Merdeka, which requires teachers to continuously adapt to digital innovations. Based on these conditions, this community service program was carried out to provide training and technological support based on Artificial Intelligence (AI) to assist teachers in completing lesson planning and student assessments. The results of the activity indicate a significant improvement in teachers’ skills in utilizing AI to enhance work efficiency and reduce administrative burdens, contributing to continuous improvement of education quality